From Critical Thinking to Argument: A Portable Guide - Barnet Sylvan (Bedford, 2008)
From Critical Thinking to Argument is a very brief but thorough guide to critical thinking and argumentation. With a dozen readings, this affordable guide can stand alone or supplement an anthology. Drawn from the widely adopted Critical Thinking, Reading, and Writing, it is the product of the authors' dual expertise in effective persuasive writing and rigorous critical thinking. It helps students move from critical thinking to argumentative and researched writing. Treatment of classic and modern approaches includes Aristotle, Toulmin, and Rogerian argument, making it a versatile text. From Critical Thinking to Argument has been revised to address current student interests and trends in argument, research, and writing.